2009
DOI: 10.1016/j.bbadis.2009.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Pathway analysis of senescence-associated miRNA targets reveals common processes to different senescence induction mechanisms

Abstract: Multiple mechanisms of senescence induction exist including telomere attrition, oxidative stress, oncogene expression and DNA damage signalling. The regulation of the cellular changes required to respond to these stimuli and create the complex senescent cell phenotype has many different mechanisms. MiRNAs present one mechanism by which genes with diverse functions on multiple pathways can be simultaneously regulated. In this study we investigated 12 miRNAs previously identified as senescence regulators. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 58 publications
6
83
0
1
Order By: Relevance
“…These functional experiments were convincingly verified by our previous findings that rs3746444C variants contributed an adverse role of prognosis in those patients with platinum-based chemotherapy. In addition, one study has reported that miR-499 had the potential to regulate the DNA damage signaling (48). Also, DNA repair-related genes and cisplatinum resistance genes, such as AKR1C3 (49,50), have higher expression in A549-miRNA-499-C cells than in A549-miRNA-499-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…These functional experiments were convincingly verified by our previous findings that rs3746444C variants contributed an adverse role of prognosis in those patients with platinum-based chemotherapy. In addition, one study has reported that miR-499 had the potential to regulate the DNA damage signaling (48). Also, DNA repair-related genes and cisplatinum resistance genes, such as AKR1C3 (49,50), have higher expression in A549-miRNA-499-C cells than in A549-miRNA-499-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results suggest that miR-34 is not only a biomarker of aging, but also an effector of aging, which might be mediated through the inhibition of autophagy genes, at least partly, through Atg9. A number of studies have investigated the miR-34 family, particularly miR-34a, whose expression increases with age in mouse and model cells in microRNA microarray analyses (Lafferty-Whyte et al 2009). Recent studies have shown that miR-34 overexpression accelerates the aging process in aging human diploid cells (IMR90) (He et al 2007) and endothelial progenitor cells (EPCs) (Zhao et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several independent lines of evidence have indicated a critical role for miRs, as biomarkers of cellular senescence, in both replicative and stress-induced modulation of in vitro cellular senescence (Lafferty-Whyte et al 2009;Poliseno et al 2008;Wagner et al 2008;Li et al 2009Li et al , 2010Olivieri et al 2009). Human umbilical vein endothelial cells (HUVECs) have been extensively used as an in vitro endothelial model representing common functional and morphological features of the in vivo endothelial cells (Unterluggauer et al 2007).…”
Section: Introductionmentioning
confidence: 99%